2009
DOI: 10.1172/jci37385
|View full text |Cite
|
Sign up to set email alerts
|

Consuming fructose-sweetened, not glucose-sweetened, beverages increases visceral adiposity and lipids and decreases insulin sensitivity in overweight/obese humans

Abstract: Studies in animals have documented that, compared with glucose, dietary fructose induces dyslipidemia and insulin resistance. To assess the relative effects of these dietary sugars during sustained consumption in humans, overweight and obese subjects consumed glucose-or fructose-sweetened beverages providing 25% of energy requirements for 10 weeks. Although both groups exhibited similar weight gain during the intervention, visceral adipose volume was significantly increased only in subjects consuming fructose.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

97
1,446
17
21

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 1,494 publications
(1,581 citation statements)
references
References 86 publications
97
1,446
17
21
Order By: Relevance
“…Baseline glucose levels reduced by 5 mg/dL, glucose area under the curve dropped by 8%, fasting insulin dropped by 10 mU/L, insulin area under the curve dropped 25%-all improved-on the same number of calories and without weight loss, just by removing the added sugar-and in just 10 days! This study alone does not prove that sugar causes metabolic syndrome, but when taken with other studies (2,26,27), Koch postulates for causation were fulfilled.…”
Section: Interventional Starch-for-sugar Exchangecontrasting
confidence: 58%
“…Baseline glucose levels reduced by 5 mg/dL, glucose area under the curve dropped by 8%, fasting insulin dropped by 10 mU/L, insulin area under the curve dropped 25%-all improved-on the same number of calories and without weight loss, just by removing the added sugar-and in just 10 days! This study alone does not prove that sugar causes metabolic syndrome, but when taken with other studies (2,26,27), Koch postulates for causation were fulfilled.…”
Section: Interventional Starch-for-sugar Exchangecontrasting
confidence: 58%
“…The recent study by Stanhope et al (2009) showing that consumption of fructose-sweetened but not glucosesweetened beverages for 10 weeks increases de novo lipid synthesis and impairs insulin sensitivity in overweight or obese adults, implicates fructose as a key nutrient that may contribute to the epidemic of metabolic disorders. The molecular links between SHBG with the risk for Page 15 of 24 A c c e p t e d M a n u s c r i p t 15 developing metabolic disorder associated diseases including hip fracture (Lee et al 2008), breast cancer (Davidson et al 1981;Key et al 1982), and coronary heart disease (Reinecke et al 2002) needs to be investigated further.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, results from clinical trials testing the effects of fructose and added sugar intake on risk of weight gain and hypertension have been inconsistent. Studies with longer duration have overall reported significant effects of sugar intake on cardiometabolic health (43)(44)(45)(46) . Several authors have recently proposed models to emphasize the capacity of fructose and fructose-derived sweeteners (sucrose, high-fructose corn syrup) to perturb cellular metabolism (47)(48)(49) .…”
Section: Discussionmentioning
confidence: 99%